(untitled) (Scientific journal of the Fergana State University, 2024)
This article focuses on economic cooperation within the realm of foreign policy of Uzbekistan. While cooperation encompasses various dimensions across political, economic, cultural, and humanitarian (social) spheres, this paper hones in on the economic aspect of collaborative efforts. Specifically, the purpose of the study is to examine how Uzbekistan engages in productive collaboration within international organizations to advance its economic interests. While discussing cooperative interactions of Uzbekistan via international organizations, the article presents a nuanced perspective. This research emphasizes Uzbekistan’s proactive role in shaping and driving cooperative endeavors on the global stage. These endeavors can be characterized as dedicated on promoting economic interests of the country. The practical significance of the analyses is to offer insights into the dynamics of economic cooperation within international organizations from the perspective of emerging discussion on ‘small states’ in international relations. The method of the study is based on systematic analysis of official documents (i.e. declarations, agreements and others), speeches, and news from official websites of Uzbekistan and international organizations. The author collected thematic patterns emerging from those sources and organized them around narratives inspired by theoretical discussions of ‘small states’ phenomenon.